A Closer Look At The EFL Students’ Grammatical Errors In Writing Descriptive Text - Maudia Rizqullah, Alifah; Sudiro, Suryo; Abdul Karim, Sayit (Universitas Cokroaminoto Palopo, 2023)
EFL students found some difficulties in writing descriptive texts because they have to observe the language features, and generic structure of such genre carefully to produce a good paragraph. Students made some errors in their writing and experienced difficulties dealing with the grammatical rules. The objectives of the present research are to identify the errors types that students might encounter in writing descriptive text and to describe what errors are dominantly made. Therefore, a descriptive qualitative research design was applied to describe students’ type of errors as proposed by Dulay (1982) and to figure out errors that dominantly occur in students’ writing, the present study used Ellis’s theory (1994), namely error collection, error identification, error description, and error explanation. The respondents were 30 students (5 males and 25 females) in English Language Education Study Program at Universitas Teknologi Yogyakarta. The research data was taken from students’ works and analyzed qualitatively. The findings revealed that students made four types of errors, ranging from the highest to lowest, namely omission, misformation, addition, and misordering. Of 174 errors, 60 errors dominantly occurred in the omission part, and 51 errors were in the misformation part. Meanwhile, 47 errors occurred in the addition part, and 16 errors occurred in the misordering part.